(untitled) (Global Journal of Management and Business Research, 2019)
Abstrak -Lombok is one of the priority areas for tourism development in Indonesia. The development of Lombok island tourism is focused on the development of halal tourism. This is in line with the award of the World’s Best Halal Honeymoon Destination and the World’s Best Halal Tourism Destination. This study aims to determine empirical evidence of the influence of customer experience and innovative value variables on halal destination image and satisfaction of tourists on Lombok Island directly or through halal destination image as a mediator. The population in this study are tourists who are on a tourist visit on the island of Lombok. The sampling technique uses convenience with the accidental sampling method, so the number of samples in this study was 126 respondents. The study found that the influence of customer experience on tourist satisfaction through a positive and significant halal destination image variable with a path coefficient of 0.075 with a significance value of 0,000 (smaller than the error tolerance standard of 0.05). While the influence of innovative value on tourist satisfaction through the halal variable destination image is positive and significant with a path coefficient value of 0.162 with a significance value of 0,000 (smaller than the standard of error tolerance of 0.05). This shows that the variable customer experience and innovative value significantly influence tourist satisfaction through halal destination image.